Has Kelantan grown faster than other states in Malaysia? A panel data analysis - Habibullah, Muzafar Shah (Penerbit Universiti Kebangsaan Malaysia, 2011)
Kelantan has been the poorest state in Malaysia for the past five decades. Despite the various Malaysian Development Plans for the past several decades, regional disparity between states remains in Malaysia. Thus, the objective of the present paper is to address the question whether Kelantan has been narrowing their income gap with other states in Malaysia. Using annual data for the period 1961 to 2003, our panel unit root test result suggest that (1) Kelantan converges towards Kedah, Negeri Sembilan, Perak, Pahang, Perlis and Selangor; (2) Kelantan is catching-up to Johor, Melaka, Penang, Sabah, Terengganu and Wilayah Persekutuan; and (3) Kelantan show divergence with Sarawak. In this respect, the government has an important role to play in enhancing growth by continuously providing stable economic environment for investment and other productive economic activities. This will ensure full convergence can take place in the future.